2015
DOI: 10.1007/s00705-015-2493-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphism of Toll-like receptor 4 and interleukin-10 in response to interferon-based therapy in Egyptian chronic hepatitis C patients

Abstract: Egypt has the highest prevalence of hepatitis C virus (HCV) in the world. It has been suggested that not only the virus but also the interaction between the virus and the host immune system is important in determining the course of the infection and the response to interferon (IFN)-based therapy. While the adaptive immune system plays a critical role in HCV infection, the innate immune system has only been recognized recently. Toll-like receptors (TLRs) form the cornerstone of the innate immune response. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 78 publications
0
16
0
1
Order By: Relevance
“…It was demonstrated that the genetic polymorphisms of TLR2 and TLR4 were not associated with asthma and allergic rhinitis, but significant association was found between these genetic variants and the disease severity in children (Hussein et al, 2012). It was revealed that TLR2 and TLR4 polymorphisms have no influence in HCV among Egyptian children (Soliman et al, 2014), while TLR4 polymorphism may be important predictor for HCV therapy in adults (Sadik et al, 2015). There was no significant association between TLR4 polymorphism and colorectal cancer (CRC), but higher serum level of it was associated with a diagnostic prospect in CRC patients (Bassuny, 2017).…”
Section: Egyptian Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the genetic polymorphisms of TLR2 and TLR4 were not associated with asthma and allergic rhinitis, but significant association was found between these genetic variants and the disease severity in children (Hussein et al, 2012). It was revealed that TLR2 and TLR4 polymorphisms have no influence in HCV among Egyptian children (Soliman et al, 2014), while TLR4 polymorphism may be important predictor for HCV therapy in adults (Sadik et al, 2015). There was no significant association between TLR4 polymorphism and colorectal cancer (CRC), but higher serum level of it was associated with a diagnostic prospect in CRC patients (Bassuny, 2017).…”
Section: Egyptian Studiesmentioning
confidence: 99%
“…However, sustained or excessive immune system activation is deleterious and leads to irreversible changes in organ structure and function (Wang et al, 2015). Toll-like receptors (TLRs) is a family of pattern recognition receptors (PRRs) that form the cornerstone of the innate immune response (Sadik et al, 2015). Toll was originally discovered as a gene controlling the dorsal-ventral polarity of the Drosophila embryo, but was later found to be involved in anti-fungal immunity (Anderson et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The TLR4 rs2149356 T allele reduces the risk of HHC compared with HCV patients and healthy controls [22]. Moreover, TT genotype frequency increased in responder patients versus non-responders to peg-IFN-α2b-ribavirin [23]. In our study, we assessed different questions from previous reports.…”
Section: Discussionmentioning
confidence: 97%
“…Thereafter, 134 articles were removed based on those containing unrelated titles, abstracts and full text, resulting in 7 eligible articles. Accordingly, only seven eligible articles were enrolled in this study for quality assessment and meta-analysis ( Figure 1) [17][18][19][20]22,23,34]. Subsequently, quality assessment was performed via NOS and included studies were shown to be of high and moderate quality (Supplemental Table 1).…”
Section: Literature Research and Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation